Radiation‐induced myofibroblastoma within the nasal sinus requiring maxillectomy and ethmoidectomy: A case report and literature review. Issue 1 (20th January 2023) - Meyer, David B.; Larkins, Michael C.; Klose, Charles; Maher, Mohammed; Zeches, Breann A.; Brodish, Brian N.; Ju, Andrew W.; Prenshaw, Karyn
Abstract: We report a case of radiation‐induced myofibroblastoma of the right nasal cavity in a patient with a remote history of radiotherapy for pediatric retinoblastoma. The patient required maxillectomy and ethmoidectomy. To our knowledge, a rare number of cases have been reported in this location. Abstract : Extramammary‐myofibroblastomas are rare tumors, especially in the head and neck region. The long‐term prognosis of these tumors post‐excision is favorable. The patient remains under close surveillance but has yet to present with clinical recurrence.